2013
DOI: 10.1002/ange.201209304
|View full text |Cite
|
Sign up to set email alerts
|

Size‐Dependent Electrostatic Chain Growth of pH‐Sensitive Hairy Nanoparticles

Abstract: Big and small, short and tall: Nanoparticles (NPs) coated with pH‐sensitive polymers underwent reversible chain growth as a result of varying electrostatic interparticle repulsion as determined by the pH value. Tuning of the pH value also enabled the coupling of differently sized NPs to form linear composite chains reminiscent of block copolymers (see picture).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Figure A shows the time evolution of the number-average degree of polymerization, X ̅ n = N 0 / N , where N is the total number of species of all sizes in the system, including monomers and chains, and N 0 is the number of monomers initially present. Figure A shows that X ̅ n scales linearly with time, which is characteristic of step-growth polymerization. ,, In the chaining of nanosized building blocks such as carbon nanotubes and gold nanorods, the step-growth polymerization mechanism ,,,, is most commonly observed, while only a few systems exhibit chain-growth or living polymerization. , In our system, each bead has comparable reactivity due to homogeneous surface functionalization and similar magnetic susceptibility. During the polymerization process, oligomers form first due to the assembly of monomers chemically linking via end-to-end interactions and then assemble into longer chains.…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…Figure A shows the time evolution of the number-average degree of polymerization, X ̅ n = N 0 / N , where N is the total number of species of all sizes in the system, including monomers and chains, and N 0 is the number of monomers initially present. Figure A shows that X ̅ n scales linearly with time, which is characteristic of step-growth polymerization. ,, In the chaining of nanosized building blocks such as carbon nanotubes and gold nanorods, the step-growth polymerization mechanism ,,,, is most commonly observed, while only a few systems exhibit chain-growth or living polymerization. , In our system, each bead has comparable reactivity due to homogeneous surface functionalization and similar magnetic susceptibility. During the polymerization process, oligomers form first due to the assembly of monomers chemically linking via end-to-end interactions and then assemble into longer chains.…”
Section: Resultsmentioning
confidence: 72%
“…Analogous to molecular subunits within polymers, colloidal particles can also be used as the self-repeating monomeric precursors, linking into 1D colloidal chains. To achieve this, various strategies have been proposed for the fabrication of colloidal chains with distinct architectures, lengths, and compositions including chemical bonding, , electrostatic interactions, ,, hydrogen bonding, directional interaction patches, ,, coordination chemistry, heat, optical traps, UV light, and external fields. ,, We have recently demonstrated the fabrication of chains that were chemically linked from beads assembled under a 1D magnetic field and have also shown that these colloidal chains can be actuated via different mechanisms upon magnetic field application. , …”
Section: Introductionmentioning
confidence: 99%
“…Overall, these spectroscopic findings indicating that the formed aggregated geometry is similar to that of due to self-assembly of NPs into one-dimensional linear chains [29]. Here, the two peaks can be ascribed to the existence of two simultaneous modes, one longitudinal and another transverse, which is associated with the surface plasmon oscillation of electron cloud along and perpendicular to the axis of one-dimensional self-assembled chain like architecture of the NPs [41]. With variation in chain length the charge distribution along the longitudinal axis, consequently, the resonance condition varies and hence the corresponding absorption peak.…”
Section: Pb 2+ Interaction and Possible Interaction Mechanismmentioning
confidence: 61%
“…Owing to charge neutralization, unfavorable electrostatic interaction with a polar solvent (in the case of water) makes them insoluble solids. On the contrary, controlled aggregation occurs due to a balanced condition between electrostatic repulsion and van der Waals attraction among nanoparticles. , On occasions, we termed this controlled aggregation as nanoparticle assemblies. Not only collective optical and electronic properties but also additional properties like dipole-induced capacitive field can be observed in the case of the assemblies of colloidal Au nanoparticles.…”
Section: Introductionmentioning
confidence: 99%